Radiation of sound waves by semi-perforated duct - TİRYAKİOĞLU, BURHAN (My University, 2022)
In this paper, the Wiener-Hopf method is studied to solve the radiation of acoustic waves from a perforated part through an infinite channel. At first the boundary value problem involving a Helmholtz equation with mixed-boundary conditions is formulated into a Wiener Hopf equation by applying the Fourier transform. After that the Wiener-Hopf kernel is split into two functions that are analytic in specified regions of the complex-plane and equation is solved analytically. Finally, numerical results showing the effect of the problem\"s parameters (channel radius, frequency, etc.) on the radiation phenomenon are graphically displayed.
Keywords: Matematik; Temel Bilimler (SCI); MATHEMATICS; Natural Sciences (SCI); Analiz; Cebir ve Sayı Teorisi; Matematik (çeşitli); Genel Matematik; Fizik Bilimleri; Analysis; Algebra and Number Theory; Mathematics (miscellaneous); General Mathematics; Physical Sciences; Fourier transform; Wiener-Flopf method; Boundary value problem; Radiation; Acoustics; MEAN FLOW; PROPAGATION; ABSORPTION; SCATTERING